2007
DOI: 10.1038/sj.emboj.7601623
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive oxygen species are essential for autophagy and specifically regulate the activity of Atg4

Abstract: Autophagy is a major catabolic pathway by which eukaryotic cells degrade and recycle macromolecules and organelles. This pathway is activated under environmental stress conditions, during development and in various pathological situations. In this study, we describe the role of reactive oxygen species (ROS) as signaling molecules in starvation-induced autophagy. We show that starvation stimulates formation of ROS, specifically H 2 O 2 . These oxidative conditions are essential for autophagy, as treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
1,515
3
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,862 publications
(1,603 citation statements)
references
References 51 publications
56
1,515
3
5
Order By: Relevance
“…Furthermore, it has recently been shown that oxygen radicals are essential for starvation-induced autophagy in vitro (Scherz-Shouval et al, 2007). For these reasons, we tested the antioxidant GCEE for its capacity to reduce oxidative stress and evidence of autophagosomal vacuole formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has recently been shown that oxygen radicals are essential for starvation-induced autophagy in vitro (Scherz-Shouval et al, 2007). For these reasons, we tested the antioxidant GCEE for its capacity to reduce oxidative stress and evidence of autophagosomal vacuole formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests the involvement of ROS in autophagy [24]. To determine if autophagy is increased in MERRF fibroblasts, first we analyzed the expression of the genes ATG12, BECLIN1, and LC3, which encode proteins involved in autophagy.…”
Section: Mitochondrial Degradation In Merrf Fibroblastsmentioning
confidence: 99%
“…Oxidative stress has been implicated in the induction of degradative autophagy [51]. It has been reported that oxidation of Atg4 at cysteine inactivates its delipidating activity on LC3, thereby leading to the induction of autophagosome formation [52]. It has also been proposed that AMPK may be activated in response to increased intracellular ROS levels, particularly through S-glutathionylation [53].…”
Section: Discussionmentioning
confidence: 99%